Emic concepts and etic paths - Engler, Steven (Religion, 2022)
This article introduces a thematic issue consisting of six case studies of emic concepts that have potential value for serving as etic concepts in the study of religion/s. It briefly reviews theoretical issues relevant to the emic/etic distinction, underlining its relative and pragmatic nature. It ends with a brief overview of the seven contributions to this thematic issue.